Description of a new species of hake: Merluccius patagonicus sp. nov. (Gadiformes, Merlucciidae) from the waters of Argentina - Lloris, Domingo; Matallanas, Jesús (Scientia Marina, 2003)
A new species of the family Merlucciidae is presented, Merluccius patagonicus sp. nov., from the waters of the Argentine Sea. Besides the description of the new species, a brief diagnosis and a key to identification are added, with the purpose of easily separating the species from its similar relatives among the genus Merluccius Rafinesque, 1810 reported in the region: M. hubbsi and M. australis.